2006
DOI: 10.3123/jemsge.28.84
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive Effects of Nobiletin against Genotoxicity Induced by 4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) in the Lung of gpt delta Transgenic Mice

Abstract: Nobiletin, a major component of citrus polymethoxy‰a-vones, possesses anticancer, antiviral and anti-in‰amma-tory activities. To evaluate the chemopreventive potential against lung cancer induced by cigarette smoke, we examined suppressive eŠects of nobiletin against genotoxicity induced by 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK), the most carcinogenic tobacco-speciˆc nitrosamine, in the lung of gpt delta transgenic mice. Male and female gpt delta mice were fed nobiletin at a dose of 100 or 500 pp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Nobiletin, a major component of citrus polymethoxy flavones, has anti-cancer effects [ 108 ]. Nobiletin inhibited CYP enzymes involved in the metabolic activation for preventing lung cancer [ 66 ]. In NNK-treated mice, oral nobiletin significantly suppressed lung tumorigenesis and decreased tumor volume [ 67 ].…”
Section: Chemoprevention Of Lung Cancer By Dietary Phytochemicalsmentioning
confidence: 99%
“…Nobiletin, a major component of citrus polymethoxy flavones, has anti-cancer effects [ 108 ]. Nobiletin inhibited CYP enzymes involved in the metabolic activation for preventing lung cancer [ 66 ]. In NNK-treated mice, oral nobiletin significantly suppressed lung tumorigenesis and decreased tumor volume [ 67 ].…”
Section: Chemoprevention Of Lung Cancer By Dietary Phytochemicalsmentioning
confidence: 99%
“…Nobiletin has been shown to reduce the genotoxicity of NNK by inhibiting CYP2A enzyme in the lung of gpt delta transgenic mice. It is important to note that NKK is metabolically activated by CYP2A enzyme to the genotoxic metabolites (69). Another study has shown that nobiletin can downregulate the mutagenic potential of food derived environmental pro-carcinogen PhIP by inhibiting CYP1A2 that is involved in the bioactivation of PhIP (70).…”
Section: Detoxification Of Environmental Carcinogensmentioning
confidence: 99%